Are we 'prescribing' MCAs correctly? A mixed method study investigating the appropriateness of MCAs initiated from hospitals within a large NHS trust. (1st April 2022) - McCarron, K; Kaur, G; Kasmani, I
Abstract: Introduction: Medication non-adherence is a significant public health issue and a drain on NHS resources, therefore an important issue for patients, policy makers and healthcare professionals. Non-adherence results in poorer health outcomes and increased hospital admissions (1). ​Multi-compartment compliance aids (MCAs) are being utilised as a 'cure all' for all causes of non-adherence when an evidence base for overall benefit is sparse. Evidence highlights that MCA introduction may only be beneficial in a few select cohorts (2). Aim: The study aim was to assess the appropriateness and patients' opinions of newly initiated MCAs for patients over 65 in hospital. Methods: A retrospective longitudinal cohort study investigated patients (≥65 years) newly initiated on MCAs in hospital. Ward-based pharmacists identified new MCA initiations between October 2020 and March 2021 across four hospital sites in a large NHS trust. Factor analysis of the data was used to identify the rationale and appropriateness of MCA initiation using UK-based assessment toolkits (NHS Tayside and 'All in Order' criteria by the University of East Anglia). Semi-structured interviews were conducted in a sample of patients prospectively via questionnaire. Interviews focussed on patients' confidence managing their medications, ability to recall their medication regime and their opinions of MCA initiation into their care. Results: Thirty new MCA initiations were identified during the data collection period with 87% (n=26) identified as inappropriate initiations according to UK-based assessment tools. Only one initiation was found to have a formal MCA assessment undertaken. Approximately two-thirds of MCAs were initiated for the introduction of home-carers via social care (67%; n=20). The next most common reasons for initiation were family requests (13%; n=4) and perceived cognitive impairment by healthcare professionals (13%; n=4), with a further 2 MCAs initiated for mobility issues (n=1) and lack of confidence (n=1). Over a third of MCA initiations (37 %; n=11) were prescribed <4 medications. Healthcare professional initiation requests commonly came from occupational therapists (37%; n=11); however, only 18% (n=2) of these were found to be appropriate. Overall, patient opinions on MCAs varied. Those with less confidence in their medicines were more in favour of their initiation; however, those more involved and understanding of their medication regime were less accepting of MCA introduction. Conclusion: A significant number of MCAs are being started for inappropriate reasons according to validated UK toolkits e.g. initiations for social care input, lack of polypharmacy and family request. Only one initiation was linked to a documented formal assessment implying further guidance and training is required for the multidisciplinary team to ensure appropriate, evidence-based provision of MCAs. Involving the patient/carer as part of a patient- centred care assessment is essential to ensure there is understanding of how to use an MCA and to reduce unwarranted 'over-prescribing' of MCAs to inappropriate patient groups. Individual patient -centred assessments may combat perceived medication non-adherence as having a 'catch all' solution. The small sample size of this study limits the ability to draw firm conclusions, especially regarding patient opinions on MCAs. References: (1) Watson SJ, Aldus CF, Bond C, Bhattacharya D. Systematic review of the health and societal effects of medication organisation devices. BMC health services research. 2016 Dec;16(1):1-3. (2) Mahtani KR, Heneghan CJ, Glasziou PP, Perera R. Reminder packaging for improving adherence to self‐administered long‐term medications. Cochrane Database of Systematic Reviews. 2011(9).